Microwave-assisted synthesis of fused piperazine-benzimidazoles via a facile, one-pot procedure. Issue 31 (29th July 2015) - Song, Gui-Ting; Li, Shi-Qiang; Yang, Zhi-Wei; Yuan, Jian-Hui; Wang, Ming-Shu; Zhu, Jin; Chen, Zhong-Zhu; Xu, Zhi-Gang
Graphical abstract: Abstract: Two series of compounds containing fused piperazine-benzimidazole scaffolds have been synthesized using an Ugi/deprotection/cyclization strategy (UDC) followed by an intermolecular nucleophilic substitution reaction. This new strategy allows for the facile synthesis of compounds in a one-pot reaction giving fused piperazine-benzimidazoles in good yields. This synthetic strategy can be readily applied to the construction of a diverse range of compounds for high throughput screening in medicinal chemistry.